Sistem Monitoring dan Kontrol Motor AC Berbasis SCADA - Ta'ali Ta'ali; Fivia Eliza (Jurnal Teknik Elektro Indonesia, 2020)
The SCADA-based AC motor monitoring and control system is a three-phase induction motor monitoring and control system. Motor speed regulation feedback is obtained from the tacho generator which is connected to the pulleys. The SCADA program manages inverter and microcontroller communications so that the process of monitoring the speed of an induction motor is done through a computer. Induction motor speed regulation using VSD as an inverter functions to adjust the source frequency so that the motor speed can be adjusted. Communication between VSD, PLC and SCADA uses the MODBUS protocol to monitor the performance of the induction motor. The main equipment uses ATV12HU22M3 inverter and CQM1H PLC. The CX-Programmer and CIMON software function to manage and monitor in real time the system. The results of the induction motor settings can be adjusted with VSD speeds ranging from 0-50 Hz. PLC as master control and SCADA function as distance controller.